AB0974 High-Field MRI: Infra-Radiological Structural Abnormalities Detection in Wrist of Patients with Spondyloarthritis and Early Rheumatoid Arthritis. (15th July 2016) - Guis, S.; Souteyrand, P.; Militianu, D.; Chagnaud, C.; Le Fur, Y.; Mattei, J.-P.; Rozenbaum, M.; Rosner, I.; Boudinet, H.; Bernard, M.; Bendahan, D.
Abstract : Background: Previous studies have showed that structural abnormalities such as erosions and geodes could be detected in wrist of patients with Rheumatoid Arthritis (RA) using high-field MRI whereas corresponding anomalies were invisible using conventional 1.5 T MRI. Similar observations have not been reported so far for patients with either an early form of RA or patients with axial and peripheral forms of spondyloarthritis (SpA). Objectives: In the present study, we compared wrist MRI investigations performed at 1.5 and 3 T in SpA and early RA patients (less than one-year disease evolution). We aimed at determining whether synovitis, geodes and erosions are similarly observed in both cases. Methods: The study was conducted in the wrist of 9 SpA patients (6 with ankylosing spondyloarthritis (AS) and 3 with psoriatic arthritis) and in 7 early RA patients. Age in the RA group ranged from 35 to 54 (6 females, 1 male) while it ranged between 22 and 64 in the SpA group (7 females, 2 males). All the patients provided their written informed consent before their inclusion in the protocol which was approved by the local ethics committee. MRI investigations were performed at 1.5T (Philips Achieva) using a Flex-M coil and at 3T (Siemens Verio) using a 4-channel flexible coil. In both cases, subjects were asked to lie down in the supine position inside the scanner and wrist was scanned at 1.5T using a T1-SE and a PD-FS-SE and at 3T using both a VIBE and a DESS sequences. MR images were analyzed by one senior radiologist (CC). Results: In the RA group, we identified more abnormalities at 3T as compared to 1.5T for 1 patient while for 5 patients the number of abnormalities was identical in both cases. 1 patient did show no abnormality. Similarly, in the SpA group, more abnormalities were observed at 3T as compared to 1.5T for 2 patients. In those cases, more erosions were identified whereas geodes, synovitis and oedema were similar. These two patients had AS with peripheral and axial pain without psoriasis. For 1 patient with structural abnormalities, the results at both fields were similar. In 6 patients, (including 2 patients with psoriatic arthritis), we did not detect any structural abnormality. Conclusions: In the present study, we illustrated that for both RA and SpA patients, MRI investigations performed at high-field can detect wrist abnormalities which were not detectable at 1.5T. Disclosure of Interest: None declared